Role of Ayurveda in the Management of Cerebral Palsy in the Children: A Critical Review - Sharma, Narinder; Gupta, Aman; Khajuria, Dheeraj (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: A group of conditions collectively known as cerebral palsy (CP) impact a person’s mobility, balance, and postural stability. Children with CP are more likely to have a motor handicap. Every 1000 live births, it happens in 1.5–2.5 of them. When compared to infants born at term, the prevalence is noticeably higher in premature births. Material and Methods: In this review, search engines such as PubMed, Ayush Research Portal, Dhara, and Scopus regarding Ayurvedic medicinal plants having Nootropic activity, Neuroprotective activity, and anticonvulsant activity were used. Results: Different single Ayurvedic medicinal drugs were screened for having nootropic activity, neuroprotective activity, and anticonvulsant activity. Discussion: These screened drugs may be used in the related conditions of CP, which in turn improves the quality of life in pediatric patients. Conclusion: More intensive scientific review on CP is the need of the hour. The present review helps in day-to-day clinical practice. A group of conditions known as cerebral palsy (CP) impacts a person’s mobility, balance, and posture. The most prevalent motor disability in children is CP. The word cerebral refers to brain related matters. Palsy is a term used to describe muscle weakness or dysfunction. A person’s inability to control their muscles due to improper brain development or damage to the growing brain is the cause of CP.[1] Although it does not necessarily result in severe problems, CP is the primary cause of childhood disability in India. A person with severe CP may require lifetime care or specialized equipment, while someone with mild CP may not require any assistance or may have minor issues like trouble walking. Since the disorder is not progressive, it does not worsen with time, and in fact,